Changes in protein abundance are observed in bacterial isolates from a natural host - Rees, Megan A.; Stinear, Timothy P.; Goode, Robert J. A.; Coppel, Ross L.; Smith, Alexander I.; Kleifeld, Oded (Frontiers in Cellular and Infection Microbiology, 2015)
Bacterial proteomic studies frequently use strains cultured in synthetic liquid media over many generations. It is uncertain whether bacterial proteins expressed under these conditions will be the same as the repertoire found in natural environments, or when bacteria are infecting a host organism. Thus, genomic and proteomic characterization of bacteria derived from the host environment in comparison to reference strains grown in the lab, should aid understanding of pathogenesis. Isolates of Corynebacterium pseudotuberculosis were obtained from the lymph nodes of three naturally infected sheep and compared to a laboratory reference strain using bottom-up proteomics, after whole genome sequencing of each of the field isolates. These comparisons were performed following growth in liquid media that allowed us to reach the required protein amount for proteomic analysis. Over 1350 proteins were identified in the isolated strains, from which unique proteome features were revealed. Several of the identified proteins demonstrated a significant abundance difference in the field isolates compared to the reference strain even though there were no obvious differences in the DNA sequence of the corresponding gene or in nearby non-coding DNA. Higher abundance in the field isolates was observed for proteins related to hypoxia and nutrient deficiency responses as well as to thiopeptide biosynthesis.